Catch her if you can : a novel [large type] - Bailey, Tessa (Bailey, Tessa. Big shots series, 2026)
Madden Donahue, the newest catcher for the Yankees, has been in love with Eve Mitchell since high school, but for some mysterious reason, the burlesque club owner always turns him down. That never stopped him from being her self-appointed protector. Case in point, now that Eve's sister has left Eve with her two children indefinitely, Madden steps in with a proposition - marry him for the much needed health benefits.